2015
DOI: 10.1038/nature14649
|View full text |Cite
|
Sign up to set email alerts
|

Parent–progeny sequencing indicates higher mutation rates in heterozygotes

Abstract: Mutation rates vary within genomes, but the causes of this remain unclear. As many prior inferences rely on methods that assume an absence of selection, potentially leading to artefactual results, we call mutation events directly using a parent-offspring sequencing strategy focusing on Arabidopsis and using rice and honey bee for replication. Here we show that mutation rates are higher in heterozygotes and in proximity to crossover events. A correlation between recombination rate and intraspecific diversity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
184
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(210 citation statements)
references
References 42 publications
20
184
5
1
Order By: Relevance
“…The mutation spectrum in the Oenothera plastome is in sharp contrast to that detected in the nuclear genome of Arabidopsis thaliana (Ossowski et al, 2010;Yang et al, 2015) or Escherichia coli (Lee et al, 2012). Mutations in nuclear genomes are biased toward single base pair G:C to A:T transitions (with a lower frequency of transversions) that are explained by deamination of methylated cytosine and UV light-induced DNA damage.…”
Section: Mutation Spectrum Of the Chloroplast Mutant Collectionmentioning
confidence: 80%
“…The mutation spectrum in the Oenothera plastome is in sharp contrast to that detected in the nuclear genome of Arabidopsis thaliana (Ossowski et al, 2010;Yang et al, 2015) or Escherichia coli (Lee et al, 2012). Mutations in nuclear genomes are biased toward single base pair G:C to A:T transitions (with a lower frequency of transversions) that are explained by deamination of methylated cytosine and UV light-induced DNA damage.…”
Section: Mutation Spectrum Of the Chloroplast Mutant Collectionmentioning
confidence: 80%
“…Because of this foreign origin, there is 2× the silentsite heterozygosity on Chromosomes XIII and IX compared with all other genomic regions in asexuals (synonymous-site heterozygosity, or Π s = 0.0442 vs. 0.0223 per site) (Tucker et al 2013), suggesting that chromosomal divergence is contributing to the increased mutation rates in this region. It has been observed that mutations accumulate at higher rates in F1 hybrids (Scavetta and Tautz 2010;Yang et al 2015), and repeat regions are more likely to change in length if the homologous sequence has a drastically divergent length (Amos et al 1996). However, perhaps most pertinent to this study is that mutations have been shown to arise at a higher rate in heterozygous regions of genomes that have interspersed homozygous and heterozygous domains (Yang et al 2015).…”
Section: The Mutational Processes Of Daphnia Pulexmentioning
confidence: 85%
“…It has been observed that mutations accumulate at higher rates in F1 hybrids (Scavetta and Tautz 2010;Yang et al 2015), and repeat regions are more likely to change in length if the homologous sequence has a drastically divergent length (Amos et al 1996). However, perhaps most pertinent to this study is that mutations have been shown to arise at a higher rate in heterozygous regions of genomes that have interspersed homozygous and heterozygous domains (Yang et al 2015). Future studies are needed to fully understand the mechanistic phenomena leading to the observed changes on D. pulex Chromosomes XIII and IX in asexual lines.…”
Section: The Mutational Processes Of Daphnia Pulexmentioning
confidence: 99%
“…S22) (54-57), might drive, or contribute to, the high rate of crossing-over in the offspring. Recent reports of higher mutation rates in heterozygotes support this possibility (58). Chaos caused by allopolyploidization also might result in multiple failures of chromosomal pairing (53).…”
Section: Discussionmentioning
confidence: 97%